Association between EPHX1 polymorphism rs1051740 and the risk of ovarian cancer: a meta-analysis - Ying Jin (Artificial Cells, Nanomedicine, and Biotechnology)
Objective We carried out a meta-analysis of case-control studies to determine whether epoxide hydrolase 1 (EPHX1) gene polymorphism rs1051740 was related to the risk of ovarian cancer.Methods Electronic databases were searched for relevant articles published in English or Chinese language. We calculated crude odds ratios (ORs) with their 95% confidence intervals (95% CIs) to assess the relationship of EPHX1 polymorphism rs1051740 with ovarian cancer risk. In addition, subgroup analyses were also conducted based on ethnicity and control source. Between-study heterogeneity was inspected with Q test and I2 statistic.Results Five eligible studies with a total of 1919 ovarian cancer patients and 1829 controls were ultimately included in the present meta-analysis. Overall results demonstrated that the association between EPHX1 polymorphism rs1051740 and ovarian cancer risk had no statistical significance either in total analysis or in subgroup analyses by ethnicity and source of control.Conclusion EPHX1 polymorphism rs1051740 may have no independent effect on ovarian cancer susceptibility.